2023
DOI: 10.1136/bmjopen-2022-070419
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender and socioeconomic patterns of awareness and usage of e-cigarettes across selected WHO region countries: evidence from the Global Adult Tobacco Survey

Abstract: ObjectivesThe study explores the awareness and e-cigarette use by demographic and socio-economic characteristics of selected 14 Global Adult Tobacco Survey (GATS) countries.DesignCross-sectional.Setting14 countries.ParticipantsSurveyed population ≥15 years selected through multi-stage cluster sampling.Primary and secondary outcome measuresWe selected 14 countries from 6 different WHO regions where GATS was conducted in different years during 2011–2017.ResultsAwareness and usage of e-cigarette were highest in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…The incomerelated difference in indoor EC/HTP exposure could be explained by the higher prevalence of ECs and HTP use among adults with higher incomes 25,26 , coupled with the perception that ECs and HTPs are less harmful and more acceptable for indoor use 27 . Although EC use is more prevalent in adults with higher education 28 , we found adolescents reporting 'Tertiary' parental education level were less exposed to SH-EC/HTP. One explanation, as has been reported previously, is that tobacco users in households with higher education level are more likely to adopt smoke-free bans at home 29 and avoid exposing their children to tobacco smoke.…”
Section: Discussioncontrasting
confidence: 61%
“…The incomerelated difference in indoor EC/HTP exposure could be explained by the higher prevalence of ECs and HTP use among adults with higher incomes 25,26 , coupled with the perception that ECs and HTPs are less harmful and more acceptable for indoor use 27 . Although EC use is more prevalent in adults with higher education 28 , we found adolescents reporting 'Tertiary' parental education level were less exposed to SH-EC/HTP. One explanation, as has been reported previously, is that tobacco users in households with higher education level are more likely to adopt smoke-free bans at home 29 and avoid exposing their children to tobacco smoke.…”
Section: Discussioncontrasting
confidence: 61%
“…Nevertheless, it is worth noting that 70% of the study participants were female, which could potentially explain the lower proportion of e-cigarette users in our study. Previous research has indicated that males were more inclined to use e-cigarettes 27,28 . This study identified perceived risk, attitudes, and policy opinions as significant predictors of e-cigarette use among university students.…”
Section: Discussionmentioning
confidence: 96%
“…Causal or temporal association between ocular symptoms and e-cigarette and cigarette use could not be determined given the observational cross-sectional study design . The findings cannot be generalized to the adolescent and young adult population outside of the US, given that our sample was restricted to US residents . While we controlled for potential confounders (age, gender, race and ethnicity, and use of other combustible substances), there might be other confounders (eg, screen time, facemask use during the COVID-19 pandemic) that can lead to increased ocular symptoms.…”
Section: Discussionmentioning
confidence: 97%